2017
DOI: 10.1159/000476002
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Liver-Type Fatty Acid-Binding Protein Level as a Predictive Biomarker of Acute Kidney Injury in Patients with Acute Decompensated Heart Failure

Abstract: Background: There are no biological markers to predict the onset of acute kidney injury (AKI) in patients with acute decompensated heart failure (ADHF). Liver-type fatty acid-binding protein (L-FABP) levels are markedly upregulated in the proximal tubules after renal ischemia. We investigated whether urinary L-FABP is a suitable marker to predict AKI in ADHF patients. Methods: We examined 281 consecutive patients with ADHF. Serum creatinine (Cr) and L-FABP levels were measured at admission and 24 and 48 h afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…It should be noted that we measured urinary L-FABP only at the point of admission to the CICU. The decision for this was based on reports of whether this is the best time for predicting AKI in patients with acute decompensated heart failure [ 36 ] or whether it is after cardiac surgery [ 37 ]. Thus, although we showed that admission measurements of urinary L-FABP may help physicians predict AKI, we do not know whether L-FABP, NT-proBNP, or a combination of both could also be used for monitoring markers.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that we measured urinary L-FABP only at the point of admission to the CICU. The decision for this was based on reports of whether this is the best time for predicting AKI in patients with acute decompensated heart failure [ 36 ] or whether it is after cardiac surgery [ 37 ]. Thus, although we showed that admission measurements of urinary L-FABP may help physicians predict AKI, we do not know whether L-FABP, NT-proBNP, or a combination of both could also be used for monitoring markers.…”
Section: Discussionmentioning
confidence: 99%
“…23 Matsumori et al 24 found that in patients with ACS high L-FABP may be useful in identifying high-risk patients for future cardiovascular events. In another study, Hishikari et al 25 examined 281 consecutive patients with acutely decompensated HF and found that L-FABP is useful for predicting the onset of acute kidney injury. Indeed, L-FABP is involved in acute kidney tubular necrosis and chronic kidney failure.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, these four proteins reflect multiorgan dysfunction, as well as systemic inflammation and immune activation. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] During the early hours of CS, changes in the expression of these proteins may precede overt multiorgan failure and identify patients at a higher mortality risk. These data highlight the relevance of systemic involvement in CS, beyond primary pump failure.…”
Section: Discussionmentioning
confidence: 99%
“…53,54 Increased urinary concentrations of L-FABP have also been described in adults with acute decompensated heart failure or surgically treated aortic aneurysm. 55,56 To date, a single promising report has been published on urinary L-FABP as a marker of AKI risk in adult patients following HSCT. 57…”
Section: New Acute Kidney Injury Indexes Liver-type Fatty Acid-bindinmentioning
confidence: 99%